Morphological evidence for dopamine interactions with pallidal neurons in primates - Eid, Lara; Parent, Martin (Frontiers in Neuroanatomy, 2015)
The external (GPe) and internal (GPi) segments of the primate globus pallidus receive dopamine (DA) axonal projections arising mainly from the substantia nigra pars compacta and this innervation is here described based on tyrosine hydroxylase (TH) immunohistochemical observations gathered in the squirrel monkey (Saimiri sciureus). At the light microscopic level, unbiased stereological quantification of TH positive (+) axon varicosities reveals a similar density of innervation in the GPe (0.19 ± 0.02 x 10^6 axon varicosities/mm^3 of tissue) and GPi (0.17 ± 0.01 x 10^6), but regional variations occur in the anteroposterior and dorsoventral axes in both GPe and GPi and along the mediolateral plane in the GPe. Estimation of the neuronal population in the GPe (3.47 ± 0.15 x 10^3 neurons/mm^3) and GPi (2.69 ± 0.18 x 10^6) yields a mean ratio of respectively 28 ± 3 and 68 ± 15 TH+ axon varicosities/pallidal neuron. At the electron microscopic level, TH+ axon varicosities in the GPe appear significantly smaller than those in the GPi and very few TH+ axon varicosities are engaged in synaptic contacts in the GPe (17 ± 3%) and the GPi (15 ± 4%) compared to their unlabeled counterparts (77 ± 6 and 50 ± 12%, respectively). Genuine synaptic contacts made by TH+ axon varicosities in the GPe and GPi are of the symmetrical and asymmetrical type. Such synaptic contacts together with the presence of numerous synaptic vesicles in all TH+ axon varicosities observed in the GPe and GPi support the functionality of the DA pallidal innervation. By virtue of its predominantly volumic mode of action, DA appears to exert a key modulatory effect upon pallidal neurons in concert with the more direct GABAergic inhibitory and glutamatergic excitatory actions of the striatum and subthalamic nucleus. We argue that the DA pallidal innervation plays a major role in the functional organization of the primate basal ganglia under both normal and pathological conditions.